INFORMATION EDUCATIONAL SYSTEMS FOR TESTING AND MONITORING STUDENTS’ KNOWLEDGE - Kondratiev, Sergey; Andreev, Anatoly; Baranova, Ekaterina; Reva, Tatyana; Petrova, Elena (Revista Inclusiones, 2019)
The experience of implementing information technologies in higher education system shows that the educational capabilities of this process can significantly improve the level and quality of training of future specialists. In the context of the implementation of modern information technologies in the educational process, the automated control of all aspects of the learning process is an important element. The purpose of the study is an analysis of the current state of the test control of students' knowledge, study of the existing computerized testing systems for monitoring knowledge and comparative analysis of some of them. The article describes the relevance of systems for testing and monitoring university students' knowledge. The analysis of the educational capabilities of computerized testing based on literary sources is performed. Based on the developed criteria, wellknown testing software for monitoring knowledge and skills of students is analyzed and rated. The conditions for ensuring the objectivity of testing results are determined.